Amplifying similarity to promote college STEM instructor–student mentoring relationship quality: a cluster randomized trial - Du, Wenyi; Lee, Hyewon; Broderick, Nicole A.; Aldana, Cristian Cervantes; Estrada, Mica; Handelsman, Jo; Maldonado, Natalia; Miller, Sarah; Patterson, Megan S.; Sandoval, Perla; Hernandez, Paul R. (Frontiers in Education, 2023)
Despite numerous (co)curricular efforts, diversifying the Science, Technology, Engineering, and Mathematics (STEM) research workforce remains challenging and large segments of the U.S. population continue to be underrepresented. Promoting instructor-student mentoring relationship quality is a potentially important mechanism to support biomedical workforce diversity, as relationship quality has been positively associated with learning and persistence. We tested the impact of a “Creating Birds of a Feather” (CBoaF) intervention designed to promote perceptions of shared similarities (psychological similarity), which in turn should promote instructor-student mentoring relationship quality. This pretest-posttest cluster randomized controlled trial was conducted with a large and diverse sample of instructors (J=15) and the undergraduates (N=567) enrolled in in their biological course-based undergraduate research experience science courses at 13 universities across the U.S. Multilevel modeling results indicated that the intervention effect on undergraduates’ perceptions of psychological similarity was moderated by pretest psychological similarity. That is, among classes with low levels of similarity at pretest, the intervention group developed stronger perceptions of posttest psychological similarity than the control group, but there were no between group differences in classes with high levels of similarity at pretest. Furthermore, the intervention exhibited a positive indirect effect on posttest instructor-student mentoring relationship quality through posttest psychological similarity. These findings highlight the potential of the CBoaF intervention to enhance undergraduate perceptions of instructor-student psychological similarity, subsequently leading to improved instructor-student mentoring relationship quality. These insights have significant implications for initiatives that aim to promote diversity and inclusion in the STEM research workforce by emphasizing the cultivation of psychological similarity between students and instructors.